PENGARUH PERSEPSI KUALITAS PELAYANAN DAN PERSEPSI NILAI TERHADAP KEPUASAN PELANGGAN (SURVEI PADA INDOMARET PALMERAH) - Wibowo, Setyo Ferry; Sarih, Iin Pusfita; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2014)
The purpose of this researchareto determine the description / overview of the perception of service quality, perceived value and customer satisfaction at Indomaret Palmerah, to examine empirically the effect of perceptions of service quality on customer satisfaction Indomaret, to examine empirically the effect of the perception of the value of the Indomaret customer satisfaction, to empirically test the influence of perceptions of service quality and perceived value together towards customer satisfaction Indomeret. The research object Indomaret customers western Jakarta branch palmerah shopping more than once a month in the period from May 2013 to January 2014. Analysis of data using SPSS software. Hypothesis testing results showed positive significant effect on the perception of service quality on customer satisfaction, the existence of a significant positive influence of perceived value on customer satisfaction, a positive significant effect on the perception of service quality and perceived value to the customer's customer satisfaction Keywords: perception of service quality, perceived value, customer satisfaction